Evaluating the economics of zero-waste retail: A case study on enhancing Indonesia’s economic diplomacy - Ekananda, Bintang; Shenindita, Nadila Putri (Priviet Social Sciences Journal, 2026)
This study evaluates the economics of the zero-waste retail market as a strategic instrument for Indonesia’s 21st-century economic diplomacy. Utilizing a qualitative case study of a pioneering waste-free refill and supermarket network, the research examines how the transition from linear to circular retail models serves as a bridge between domestic sustainability policy and international economic engagement. Through SWOT analysis and an assessment of closed-loop logistics, the article analyzes the internalization of environmental externalities and the resulting competitive advantages in carbon mitigation and energy efficiency. Beyond operational metrics, the study explores how the scalability of the zero-waste retail market generates reputational capital for Indonesia. This empirical validation is positioned as a source of bargaining power for Indonesian diplomats navigating the UN Treaty on Plastic Pollution, providing a credible domestic 'proof of concept' for reuse-based economies in the Global South. However, the study also addresses the economic fragility of the model, specifically the trade-offs in reverse logistics and the infrastructure requirements for high-functioning reuse systems. By balancing economic viability with strategic foreign policy aims, the research concludes that zero-waste retail infrastructure acts as a pivotal instrument for state-led ESG leadership in an increasingly fragmented global trade environment.